1994
DOI: 10.1007/bf02416994
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of benign fatty tumors in children: report of four cases and review of the literature

Abstract: This study correlates the magnetic resonance imaging characteristics with the pathologic findings in rare benign fatty soft tissue tumors in four children. A review of the literature is presented. Two cases of infiltrating lipoma displayed bright signal on both T1- and T2-weighted images, similar to that observed in subcutaneous fat. Histological study revealed extensive muscle infiltration by mature fat, with some areas of total fatty replacement. The case of facial lipomatosis revealed an extensive process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…Reports of MRI in children with lipoblastoma, however, are limited. 11 Histopathologically, it differs from the myxoid liposarcomas by its characteristically lobular structure, devoid of pleomorphic cells with hyperchromatic nuclei or giant cells. In recently conducted cytogenetical studies, an anomaly in chromosome 8 q has been reported in lipoblastoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of MRI in children with lipoblastoma, however, are limited. 11 Histopathologically, it differs from the myxoid liposarcomas by its characteristically lobular structure, devoid of pleomorphic cells with hyperchromatic nuclei or giant cells. In recently conducted cytogenetical studies, an anomaly in chromosome 8 q has been reported in lipoblastoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…These singular findings correlate with immature and mature adipose, myxoid areas and areas of cystic degeneration. [27][28][29][30] Thus, MRI seems to be a reliable radiologic tool. Lipoblastoma must be suspected in a child < 3 years of age with a predominantly fatty, nonhomogeneous, soft tissue mass on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The presenting symptoms relate to the size and location of the mass, but the mass itself is not painful [ 42 ]. Left alone, they mature into a benign lipoma [ 43 ]. Histologic evaluation reveals a spectrum of fat cells in various stages of maturation, ranging from lipoblasts to mature adipocytes, embedded in a variable amount of myxoid stroma; the myxoid component is anecdotally more prominent in very young patients [ 42 ].…”
Section: Fatty Lesions Lipoblastoma/lipoblastomatosismentioning
confidence: 98%